2018
DOI: 10.1016/j.omtn.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

miR-93-5p-Containing Exosomes Treatment Attenuates Acute Myocardial Infarction-Induced Myocardial Damage

Abstract: Adipose-derived stromal cells (ADSCs) have been considered as an attractive therapeutic tool. Accumulating evidence indicates that the healing effects of ADSCs are mainly related to paracrine action rather than transdifferentiation. Data show that the expression of miR-93-5p has a cardio-protective effect after acute myocardial infarction (AMI). To identify whether miR-93-5p-encapsulating exosomes that form ADSCs have a better cardio-protective effect, we investigated the inflammatory factors and miR-30d-5p ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(121 citation statements)
references
References 47 publications
2
119
0
Order By: Relevance
“…Increasing evidence has indicated that the EV microRNA (miRNA) content as one of their most likely paracrine mechanism(s) of action. Several miRNAs have been associated with MSC-EV cardioprotective, pro-survival and angiogenic effects, including, for example, miR-21 [187]; miR-125b [188]; miR-320d [189]; miR-95-3p [190]; miR-210 [191]; miR-29 and miR-24 [180]. Additionally, EVs have been shown to biochemically restore ATP and NADH levels and redox state within the injured tissue [192].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has indicated that the EV microRNA (miRNA) content as one of their most likely paracrine mechanism(s) of action. Several miRNAs have been associated with MSC-EV cardioprotective, pro-survival and angiogenic effects, including, for example, miR-21 [187]; miR-125b [188]; miR-320d [189]; miR-95-3p [190]; miR-210 [191]; miR-29 and miR-24 [180]. Additionally, EVs have been shown to biochemically restore ATP and NADH levels and redox state within the injured tissue [192].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
“…Pharmacological priming by atorvastatin, a well-established lipid-lowering drug that can enhance stromal progenitor cell cardioprotective effects, has also been reported [196]. Another well-accepted approach is to increase EV function via genetic overexpression of specific miRNAs within parental MSC as vesicle cargo loading strategy; as result, a significant fold enrichment of those regulatory miRNAs putatively involved in EV paracrine ability has been observed, thus enhancing their phenotypic effects on responder cells [189,190,197].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
“…Hence, circulating cardiac exosomes that contain abundant amounts of cardiac‐specific miRNAs could not only serve as diagnostic biomarkers but might also be very helpful in cell‐free cardiotherapy and regeneration of the post‐infarct myocardium . One study suggested that after AMI, miR‐93‐5p‐enhanced adipose‐derived stromal cells in exosomes could prevent cardiac injury by inhibiting autophagy and the inflammatory response . When delivered to the ischaemic myocardium from remote ischaemic organs, exosomal miRNAs could provide a protective response against apoptosis by regulating autophagy and increasing miR‐144 expression in circulating exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…49 One study suggested that after AMI, miR-93-5p-enhanced adipose-derived stromal cells in exosomes could prevent cardiac injury by inhibiting autophagy and the inflammatory response. 51 When delivered to the ischaemic myocardium from remote ischaemic organs, exosomal miRNAs could provide a protective response against apoptosis by regulating autophagy 52 and increasing miR-144 expression in circulating exosomes. Furthermore, remote ischaemic preconditioning suppressed the autophagy negative regulator pmTOR, thus reducing infarct size and improving cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly increased angiogenesis is induced by the presence within EVs of the extracellular matrix metalloproteinase inducer EMMPRIN, VEGF, MMP9 and miRNA-210 [172,173]. Other miRNAs involved in myocardium protection are miRNA-21a-5p, miRNA -21, miRNA-125-5p and miRNA93-5p [174][175][176][177]. Besides, overexpression of miRNA-30d inhibited autophagy and promoted polarization of macrophages into the anti-inflammatory M2 type [169].…”
Section: Extracellular Vesicles-based Regenerative Medicinementioning
confidence: 99%